JAMINAN SOSIAL DALAM PANDANGAN IBNU HAZM DAN RELEVANSINYA DENGAN PENGEMBANGAN JAMINAN SOSIAL DI INDONESIA - Wartini, Atik (Hunafa: Jurnal Studia Islamika, 2014)
This research is library research that discusses the thought of Ibn Hazm. This research focuses on the study of the methodology of ijtihad of Ibn Hazm. One of the themes of ijtihad of Ibn HazmÂ  can still, up to the present, be considered is his concept on social assurance.Â  Ibn Hazm is the follower of the School of áºairiyyah who emphasizes more on text of the reality and in some matters rejects qiyas. Therefore, his thought on social assurance Â is of importance to study. This research studies the method of ijtihÄd of Ibn Hazm, his istidlÄl and the influence of the School of Zhairiyyah on his ijtihad as well as his istinbÄá¹ Â or Â ijtihÄd on social assurance Â for the haves not. Ibn Hazm possesses liberal interpretation to Â social assurance. Therefore, his thought on social assurance is of importance to study, particularly when related to the development of the contemporary Islamic Law and to the BPJS that currently growsÂ  Â in Indonesia.Kata Kunci : áºahiriiyah, Ibnu Hazm, Ijtihad, BPJS.